Work and Family Interface in the International Career Context - Mäkelä, Liisa (Springer, 2015)
This book focuses on the interface of work and personal life of international professionals. The globalization of business has led to an increasing number of people who work in international roles either through working abroad on different kinds of assignments or through international travelling. This book provides novel knowledge on the topic from different perspectives, highlighting not only the inherent challenges but also the positive side of working in a modern globalized world. Moreover, the book contributes by bringing together international professionals’ own experiences, family members’ experiences, organizational aspects and new theoretical discussions and models. The book covers several different perspectives on the work and personal life interface offering insights on the areas like adjustment, social support, dual-career issues and organizational practices. The book examines the situations of several different types of international employee such as organizational expatriates, self-initiated expatriates and international business travellers. The new interesting research evidence is provided from various country contexts from North America, Europe and Asia by researchers around the world.